2006
DOI: 10.4103/0250-474x.27832
|View full text |Cite
|
Sign up to set email alerts
|

Reverse-phase high performance liquid chromatographic determination of Tizanidine and Valdecoxib in tablets

Abstract: A simple, reproducible and efficient reverse-phase high performance liquid chromatographic (HPLC) method was developed for simultaneous determination of tizanidine and valdecoxib from their pharmaceutical dosage forms. Separation was done by using mobile phase of composition ammonium acetate buffer (0.1 M): methanol: acetonitrile in the ratio of 50:30:20 v/v. Quantitation was achieved with UV detection at 232 nm based on peak area, with linear calibration curves at concentration ranges from 1-100 µg/ml for tiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…United States Pharmacopeia (USP) have analytical methodologies involving TZ, using high performance liquid chromatography (LC) for related compounds determination (USP 39, 2016). Studies using LC have been reported with tizanidine alone or in association with other drugs, but there isn`t one using association with charged aerosol detector (CAD) (2,(5)(6)(7)(8). CAD detector is a new type of detector introduced for LC applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…United States Pharmacopeia (USP) have analytical methodologies involving TZ, using high performance liquid chromatography (LC) for related compounds determination (USP 39, 2016). Studies using LC have been reported with tizanidine alone or in association with other drugs, but there isn`t one using association with charged aerosol detector (CAD) (2,(5)(6)(7)(8). CAD detector is a new type of detector introduced for LC applications.…”
Section: Introductionmentioning
confidence: 99%
“…It recently began to be widely used in pharmaceutical analysis (9,10). It has been compared to other detectors, such as the ELSD (evaporative light scattering detector), RI (refractive index), UV (ultraviolet) and MS (mass spectrometry), and has been found to be more sensitive and reproducible than ELSD and to exhibit more uniform response factors (7,(11)(12)(13). CAD is able to analyze a wider range of analytes than the UV detector due to its ability to detect non-chromophoric compounds, including counter-ions of drugs (14).…”
Section: Introductionmentioning
confidence: 99%
“…Different methods have been used for the determination of VALD in products and biological samples such as high-performance liquid chromatography (HPLC) [10][11][12][13][14][15][16][17][18][19][20][21][22][23], and spectrophotometry [24][25][26][27][28][29]. No potentiometric methods have yet been reported for the determination of VALD.…”
Section: Introductionmentioning
confidence: 99%